Association of Tobacco Products Use and Diabetes Mellitus-Results of a National Survey Among Adults in Saudi Arabia - Abdalla Abdelwahid Saeed (Balkan Medical Journal, 2012)
Objective: To compare the tobacco products use patterns of known diabetics and non diabetics. Material and Methods: A community-based cross-sectional study using STEPwise approach among adults using a multistage, stratified, cluster random sample. Data was collected using a questionnaire which included sociodemographics; tobacco products use habits, history of diabetes, biochemical and anthropometric measurements.Results: Of the total of 4654 subjects who participated in the study, 1016 (21.8%) were ever smoked tobacco products users and 65 (1.4%) were ever smokeless tobacco products users. Known Diabetes prevalence was 15.3% (712 known diabetics). There were no significant differences in diabetic status and smokeless tobacco products use for both ever and current use. For smoked products diabetics are fewer in current smokers and more in ex smokers. Diabetics started smoking significantly older, smoked for longer duration and higher intensity than non diabetics.Conclusion: Diabetes appears to be associated with smoked but not smokeless tobacco products use.